New Late Pennsylvanian Paleomagnetic Results From Paraná Basin (Southern Brazil): Is the Recent Giant Gaussian Process Model Valid for the Kiaman Superchron?. Issue 7 (10th July 2019) - Brandt, Daniele; Ernesto, Marcia; Constable, Catherine; Franco, Daniel Ribeiro; Carlos Weinschutz, Luiz; de Oliveira Carvalho Rodrigues, Pillar; Hinnov, Linda; Jaqueto, Plinio; Strauss, Becky E.; Feinberg, Joshua; de Paiva Franco, Pedro Vitor; Zhao, Xixi
Abstract: The most recent Giant Gaussian Process (GGP) model, based on the last 5 Ma, has been used as a reference for directional distribution of paleomagnetic record of older rocks as Cenozoic and Proterozoic. However, for Paleozoic times, its validity has not yet been tested. Here we evaluate the validity of this recent GGP model for the Kiaman superchron. We present new paleomagnetic results from a late Pennsylvanian section of glacial rhythmites (Mafra Formation) from southern Brazil. The 5‐m section sampled spans more than 800 kyr, as evaluated by cyclostratigraphic analysis. Thermal demagnetization revealed a reversed characteristic component carried by single domain magnetite. Anisotropy of anhysteretic remanent magnetization indicated a small shallowing correction of f = 0.97. The final paleomagnetic pole position is located at 51.9°S, 344.3°E ( N = 111, R = 109.0, K = 55.9, A 95 = 1.8°), with a mean direction of Dec = 144.2°, Inc = 69.5° ( N = 111, R = 110.2, k = 134.4, α 95 = 1.2°, Paleolat = 53.2°S). The shape of the distribution of magnetization directions (elongation E = 2.08 1.44 3.13 ) and the dispersion of virtual geomagnetic poles ( S V = 10.9 9.8 11.8 ) are incompatible with the recent model. The reduced dispersion, also found in other studies, implies a different shape in directional distributions for any GGP model describing the Kiaman interval. This result alerts us that we should abandon the use of the recent GGP model as a reference for inclination shallowing correction of Carboniferous sedimentary data. Key Points: We present a new Upper Carboniferous paleomagnetic pole for South American Plate, with inclination shallowing correction and time control The paleosecular variation results indicated that we should avoid the use of recent geomagnetic models as a reference for Kiaman superchron